1967
DOI: 10.1037/h0020107
|View full text |Cite
|
Sign up to set email alerts
|

Shifting attention between modalities: A comparison of schizophrenics and normals.

Abstract: An index of intermodal attention switching, A, derived from RT procedures with multiple stimuli, a single response, and 2 levels of stimulus certainty, was used to compare the performance of 12 normal and 12 schizophrenic Ss. Schizophrenics had significantly more difficulty switching attention between modalities than normals. It cannot be determined on the basis of these data whether intermodal switching time is longer for schizophrenic Ss, or whether the signal to switch attention is not picked up as reliably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

1970
1970
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 4 publications
4
29
0
Order By: Relevance
“…Our crossmodal result partially confirms the greater crossmodal retardation by brain-damaged patients compared to controls reported by Benton et al (1962) except that they observed this only in RTs to lights. Their patient group contained few, if any, CHI cases and so is not comparable to the present sample Studies of schizophrenia (Kristofferson, 1967;Zahn et al, 1997) and ADHD (Zahn et al, 1991) have found significant or marginal effects for modality uncertainty but not for crossmodal retardation. Thus the VS -Reg comparison seems to be more sensitive to attention impairments than the crossmodal effect.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our crossmodal result partially confirms the greater crossmodal retardation by brain-damaged patients compared to controls reported by Benton et al (1962) except that they observed this only in RTs to lights. Their patient group contained few, if any, CHI cases and so is not comparable to the present sample Studies of schizophrenia (Kristofferson, 1967;Zahn et al, 1997) and ADHD (Zahn et al, 1991) have found significant or marginal effects for modality uncertainty but not for crossmodal retardation. Thus the VS -Reg comparison seems to be more sensitive to attention impairments than the crossmodal effect.…”
Section: Discussionmentioning
confidence: 71%
“…Previous research has found that RT is faster under constant modality conditions (Kristofferson, 1967) suggesting that persons attend to or prepare optimally for stimuli in just one modality at a time so that RT is retarded when a stimulus occurs in the unattended channel. A larger increment in RT under variable modality conditions would suggest a difficulty in shifting attention between modalities.…”
Section: Experiments 2 Simple Rt To Tones and Lightsmentioning
confidence: 97%
“…Moreover, since the same task was undertaken regardless of stimulus modality, these performance costs could not be confused with task-switching effects (Rogers & Monsell, 1995). It seems, therefore, that the modalityswitching costs described here reflect a processing penalty in having to switch attention between the two modalities (Kristofferson, 1967;LaBerge, 1973). The standard repetition effect therefore reflects different processes from those responsible for directing attention to a particular modality.…”
Section: The Standard Repetition Effect and The Modality Repetition Ementioning
confidence: 99%
“…Moreover, in cases where the modality repetition effect has been found, problems exist over its interpretation. As Spence and Driver (1997) have pointed out, although many have postulated that the modality repetition effect may reflect the cost of having to switch attention between the sensory modalities (e.g., Kristofferson, 1967), a more mundane explanation may suffice. For instance, in cases where simple RTs were measured, subjects may have lowered their criterion for a response on ipsimodal relative to crossmodal trials (Spence & Driver, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation